แนวทางการพัฒนาแบบจำลองสารสนเทศอาคาร (BIM) เพื่อคำนวณค่าการถ่ายเทความร้อนรวมของผนังด้านนอกของอาคาร (OTTV) ในขั้นตอนการออกแบบเบื้องต้น - อภิเกียรติ เจริญสุทธิโยธิน (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
According to the Energy Conservation Promotion Act B.E. 2550, Overall Thermal Transfer Value (OTTV) could be calculated in various ways such as manual calculation, or programme BEC V.1.0.6. However, it was found that the current program would receive a large number of data from the designers and can be changed all the time. This can give rise to errors in the input data. Thus, to preclude this problem, the algorithm in Autodesk Revit programme coupled with the Dynamo add-ins with the goal to generate commands capable of controlling and retrieving data, and mathematical calculations, which can generate the result of the OTTV equation in accordance with The Ministerial Regulation of Energy B.E. 2552 has been developed. Moreover, the result of this development is the add-ins programme for estimating OTTV in the schematic design stages in which users can adjust the design and the value would then be changed automatically, the results are shown in various forms and suggest improvements to the building, thus reducing the overlapping processes. Compared to the BEC V.1.0.6 programme, it was found that the estimated OTTV value generated by the Dynamo add-ins has an approximate deviation of ±1% for solid walls and windows without shading devices due to the different linear interpolations which cause the difference in the results. Then, windows with shading device, the error has an approximate deviation of ±3% due to the calculation of the shading coefficient from the Dynamo with The Ministerial Regulation of Energy B.E. 25529, the lack of calculation for shading device to protect the diffuse radiation of the sun. Therefore, comparing the calculation results of the Dynamo with the BEC programme. It has a high calculation result.